Accountability and intensification of teaching work in Pernambuco’s full-time high school (Práxis Educativa, 2014)
In this paper, we present partial results of the research Teaching Work and Full-time Education in High School. The aim was to identify the processes of accountability in a full-time education program (Programa de Educação Integral - PEI), implemented in Pernambuco’s Reference Schools of high school, and their influences on the conditions of the teaching work. Through document analysis, we infer that the choice made by Pernambuco’s government is anchored in a managerialist, neoproductivist and neotecnicist perspective of management that guides all this process of change. This perspective induces the teaching work through an intense process of responsibility, or accountability, which effects are highlighted by Freitas (2012). Keywords: Teaching work. High school. Full-time education.